The music industry and the internet: A decade of disruptive and uncontrolled sectoral change - Ulrich Dolata (Universität Stuttgart, Institut für Sozialwissenschaften, Abteilung für Organisations- und Innovationssoziologie, 2011)
Since the late 1990s, the music industry has been undergoing a period of significant and crisis-ridden changes. This period was launched and driven forward by a new set of technologies:digitalization, data compression and the Internet. This paper analyzes the repercussions of this new technological constellation on the socio-economic structures and institutions of this sector. The depiction of this technology-driven sectoral transformation shows that at that time the constitutive impulses for restructuring came from the not well-established fringes of the sector and from external actors. The established companies of the music business were hesitant in accepting the new technological challenges. They initially reacted with blockades and containment strategies and only defined a strategic repositioning upon massive and undeniable pressures to change. The paper argues that the low ability to anticipate and adapt to these technological, organizational and institutional challenges is based on the interplay of several factors. Among these are: (1) general difficulties in anticipating the socio-economic impact of fundamentally new technological opportunities; (2) complex and time-consuming processes of establishing a new techno-institutional match; (3) technological conservatism; (4) the oligopolistic structure of the sector; as well as (5) the hierarchically structured focal companies. Together these factors obstructed a controlled sectoral transformation orchestrated by the established core players. – – Die Musikindustrie befindet sich seit Ende der 1990er Jahre in einer tiefen und anhaltenden Restrukturierungskrise, die maßgeblich durch ein neues Set an Technologien - Digitalisierung, Datenkomprimierung und das Internet - angestoßen worden ist. In diesem Text werden die Wirkungen dieser neuen technologischen Konstellation auf die sozioökonomischen Strukturen und Institutionen des Sektors sowie auf die Handlungsorientierungen seiner Kernakteure untersucht. Die Rekonstruktion des technikgetriebenen Wandels der Musikindustrie zeigt, dass die wesentlichen Impulse der Restrukturierung von den Rändern des Sektors beziehungsweise von sektorexternen Akteuren ausgingen - und nicht von den etablierten Musikkonzernen. Diese haben die neuen technologischen Herausforderungen sehr zögerlich aufgenommen, darauf zunächst vor allem mit Blockadehaltungen und Eindämmungsstrategien reagiert und erst vor dem Hintergrund eines massiven und unabweisbaren Veränderungsdrucks damit begonnen, sich strategisch neu zu positionieren. Die geringe Antizipations- und Adaptionsfähigkeit der zentralen Akteure der Musikindustrie wird aus dem Zusammenspiel mehrerer Faktoren erklärt. Neben (1.) generellen Schwierigkeiten der Antizipation grundlegend neuer technologischer Möglichkeiten und (2.) aufwändigen Prozessen der Etablierung neuer, zu ihnen passender institutioneller Rahmenbedingungen haben (3.) der technologische Konservatismus und (4.) die oligopolistische Struktur des Sektors zusammen mit (5.) den hierarchischen Organisationsstrukturen seiner führenden Unternehmen einen vom Kern des Sektors ausgehenden und durch ihn kontrollierten Wandel blockiert.
urn:nbn:de:bsz:93-opus-62707
Keywords: 300